Increasing public safety at pedestrian crossings as an element of improvement in quality of life - Zakrzewska-Półtorak, Alicja; Szulc, Anna (Poprawa bezpieczeństwa na przejściach dla pieszych jako element podnoszenia jakości życia, 2021)
The main aim of the article is to discuss the results of a survey among car drivers regarding safety at pedestrian crossings. An integral part of the paper was the assessment of that safety in the context of improvements in the public’s quality of life, complete with presentation of the innovative approaches, particularly those involving the modernization of lighting solutions adopted for the purpose. The study put emphasis on pedestrian safety in municipal and suburban areas in Poland, based on data obtained for the period 2019-2020, for which the following methods were employed: descriptive method, simple statistical methods, questionnaire survey. Traffic incidents involving pedestrians are decidedly more fatal in non-urbanized areas – higher mortality. The proper lighting of roads, particularly pedestrian crossings, significantly contributes to the increase of public safety in traffic,of special importance is the effective choice of light colour, intensity, and oscillation (pulse).
Biblioteka Regionalisty, 2021, Nr 21, s. 148-159
Keywords: road safety; quality of life; road accidents; lighting of pedestrian crossings; bezpieczeństwo na drogach; jakość życia; wypadki drogowe; oświetlenie przejść dla pieszych